The Existence of Health Literacy in Science Education: A Systematic Literature Review - Fitrah Amalia Salim; Susriyati Mahanal; Hendra Susanto (Jurnal Penelitian Pendidikan IPA, 2024)
Health literacy is an interesting thing to study in science learning.  The purpose of this Systematic Literature Review (SLR) is to determine the trend of health literacy publications in scopus indexed journals and the potential for empowering health literacy in science learning. The keywords used were "health literacy" and "student" on the search menu in the scopus database and met the criteria for further analysis as many as 22 articles. Researchers use the PRISMA model to include and exclude articles. The findings obtained are the trend of health literacy publications in science learning in the form of types of research, year distribution, keywords, researcher nationality and international collaboration. The potential for health literacy in science learning can enrich students' knowledge about disease prevention, the integration of science learning with technology can improve students' skills in obtaining health information, community involvement with science learning has the potential to increase student awareness and responsibility, innovative science learning supports the empowerment of student health literacy. The implication in this study is that health literacy can be empowered through innovative learning models in science learning.